Split crest technique: An effective method in dental implantology for narrow ridges: A case report - Biočanin Vladimir; Pejanović Đorđe; Antonijević Đorđe; Ćirić Marija; Tambur Zoran; Zarić Svetislav (Serbian Medical Society - Dental Section, Belgrade, 2023)
Introduction Implant placement with simultaneous bone augmentation presents procedure with high risk of complications. In those situations, one of the surgical procedures with promising outcomes is the split crest technique. Case report A 69-year-old edentulous patient was referred to the Clinic of Oral Surgery, at the Faculty of Dentistry in Pancevo. The width of the mandibular alveolar ridge in the inter-canine region was 2 mm. For the ridge splitting and expansion, a special split and expansion kit was used (Esset Kit® , Osstem, South Korea). The procedure started with crestal remover carbide cylindrical bur of 7 mm diameter for flattening of the alveolar ridge to the width of 4 mm. Then, a sharp lance drill was used to mark the places for implant osteotomies and placement. After that, 1.8 mm twist drill was used to prepare a bed of 10 mm depth, and a 13 mm saw was directed vertically. Set of expansion drills were used to expand the alveolar ridge gradually. Two implants 3.5x10 mm each (TSIII SA® , Osstem, South Korea) were inserted in the region of lower canines and the space between split buccal and lingual bone lamellae remained empty. Initial stability of inserted implants was assessed by implant stability quotient (ISQ). The values for implant stability were high for both inserted implants (98 and 93). After the surgical procedure, a control CBCT was done. The wound healed uneventfully. Conclusion Split crest technique seems to be a predictable alternative for implant placement in narrow alveolar ridges.